The mental unfoldment of the child - McCoy, Rose Margaret (My University, 1903)
Repeated reversals of stress, alternate tension and compression, is less common. A familiar example is the reciprocating parts of an engine, piston rod and connecting rod. The most important case of such stresses in structural work is in the end posts and end top and bottom chords of a draw span truss. For instance, the end posts are in tension when the span is swung, and in compression when the span is closed and a train passes over. Some of the best engineering authorities specify in the case of tension and compression occurring in the same member, that their sum shall be taken in obtaining the allowable working stress. Other engineers hold that the effect of alternate stresses of opposite sign is not equivalent to a stress in either direction equal to their sum, and such a rule involves an excess of material. Without discussing the case in question, or any of the many formulas used for obtaining the working stress; it is sufficient to say that the elastic limit and the ultimate strength are the bases of them all. The effect repeated tension and compression have in lowering the elastic limit or ultimate strength of the material must be determined by trial. In this test the object has been to approach the conditions of the members in the truss of a draw span as nearly as possible. It is not practical to apply to a test specimen the number of repetitions of stress that would occur in the life of a bridge, so in this test a greater stress was applied with a fewer number of repetitions, thus working the metal as hard, or nearly so, as actual service would do. We tried to bring the stress in tension as near as possible to the elastic limit without reaching it.
Citation: McCoy, Rose Margaret. The mental unfoldment of the child. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Child Development; Education; Morality; Theses